Connecting the Dots: Engaging Wider Forms of Openness for the Mutual Benefit of Musicians and Musicologists - Gotham, Mark R. H. (Empirical Musicology Review, 2021)
While it is encouraging to see renewed attention to 'openness' in academia, that debate (and its interpretation of the F.A.I.R. principles) is often rather narrowly defined. This paper addresses openness in a broad sense, asking not so much whether a project is open, but how open and to whom. I illustrate these ideas through examples of my own ongoing projects which to seek to make the most of a potential symbiosis between academic and wider musical communities. Specifically, I discuss how these communities can both benefit from – and even work together on building – highly accessible and interoperable corpora of scores and analyses when ambitious openness is factored into decision making from the outset.